Investigation on the accurate parameter estimation of photovoltaic (PV) module based on simplified two-diode model. (13th June 2016) - Chitti Babu, B.; Gurjar, Suresh; Cermak, Tomas
Abstract : Purpose: This paper aims to present a detailed investigation on the parameter estimation of a photovoltaic (PV) module by using a simplified two-diode model. Design/methodology/approach: The studied PV module in this paper resembles an ideal two-diode model, and to reduce the computational time, the proposed model has a photocurrent source and two ideal-diodes and neglects the series and shunt resistances. Hence, for calculating the unknown parameters, only four parameters are required from the datasheet. Moreover, the studied model is simple and uses an easy modeling approach which is free from complexities. Findings: The performance of the PV module is analyzed under non-standard test conditions by considering partial shading at different shaded levels, and it is found that the model has less computational time and gives accurate results. Originality/value: The usefulness of this PV model is demonstrated with the help of several illustrative figures, and the performance of the PV module is evaluated.